Efficient Interfacial Upconversion Enabling Bright Emission at an Extremely Low Driving Voltage in Organic Light‐Emitting Diodes (Advanced Optical Materials 4/2022). Issue 4 (18th February 2022) - Izawa, Seiichiro; Morimoto, Masahiro; Naka, Shigeki; Hiramoto, Masahiro
Abstract : In article number 2101710, Seiichiro Izawa, Masahiro Morimoto, Shigeki Naka, and Masahiro Hiramoto report an efficient organic light‐emitting diode (OLED), operable by a 1.5‐V battery, that produces bright emission equivalent to the luminance of a typical display. The OLED is based on an upconversion transition through triplet–triplet annihilation near its donor/acceptor interface. The efficient upconversion is realized by controlling the character of an interfacial charge transfer state, which is a key intermediate.